Social Science Research Findings and Educational Policy Dilemmas - Miller, Steven I.; Fredericks, Marcel (Education Policy Analysis Archives, 2000)
The article attempts to raise several distinctions regarding the presumed relationship of social science research findings to social policy making. The distinctions are made using Glymour's critique of the Bell Curve. An argument is made that (1) social science models and research findings are largely irrelevant to the actual concerns of policy makers and (2) what is relevant, but overlooked by Glymour, is how ideological factors mediate the process. The forms that ideological mediation may take are indicated.